Study of Physical Chemical Properties of Drilling Solution - M. K. Urozov; O. X. Qulmuminov; B. B. Ochildiyev; S. A. Xolmurоdova (Researchparks Publishing, 2021)
Material balances, material flow schemes, technological schemes of production of cellulose suitable for chemical processing on the basis of wastes of local raw materials and textile enterprises and polyanionic cellulose on its basis are created.